THE IMPACT ON THE INHERITANCE OF NOMINEE ARRANGEMENT IN INDONESIA TO THE THIRD PARTY OF SHARE BUYERS - Wibowo, Ari Tri; Prihartinah, Tri Lisiani (Faculty of Law, Universitas Jenderal Soedirman, 2021)
Plenty of the nominee arrangement traditions in Indonesia become obstacles to the nominee arrangementâ€™s trade chiefly when the inheritance of nominee arrangement is previled. This study examines the legal repercussion of nominee arrangement to the third parties of share buyers. This study used normative juridical approach. Then, the legal evidence were collected through literature reviews study and documents. The result has indicated that the existence of nominee arrangement inheritance can precipitate to law on share buying, exclusively the trade of share is carried out by the beneficiary without the awareness of the nominee or the nominee's inheritance. The third party who buys the shares will have a large legal impact.Â Keywords: Legal impact, inheritance, Nomine Arrangement